Primary erythromelalgia caused by SCN9A gene mutation: A case report and literature review - Cuicui SUN; Sai YANG; Hang ZHENG; Yunsheng LIANG; Zhimiao LIN; Yongfeng CHEN (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To report a case of hereditary skin disease mainly characterized by burning pain of the lower legs and feet, accompanied by flush and elevated skin temperature, and to identify the pathogenic genes and mutation sites in order to explore effective treatment methods. Methods The clinical data of the case were collected and peripheral blood was taken from the patient and relatives to extract genomic DNA. Next-generation sequencing of hereditary skin disease genes was performed, and suspected pathogenic mutations were verified with Sanger sequencing. The patient was treated with aspirin for anti-inflammation, rizatriptan benzoate tablet, mexiletine hydrochloride, carbamazepine, local injection of botulinum toxin analgesia, topical compound polymyxin B ointment and cooling therapy. Results A heterozygous mutation of SCN9A:NM_002977.3:c.688+142G>A or SCN9A:ENST00000375387.4:c.626G>A was detected in the patient's peripheral blood genomic DNA. The same mutation was found in the patient's sister, an uncle and a cousin. Based on the pathogenic gene and clinical manifestations, the patient was diagnosed with primary erythromelalgia (PEM). After the treatment, the pain was significantly alleviated. Conclusions The intron mutation of NM_002977.3:c.688+142G>A or missense mutation c.626G>A(p.Gly209Asp) of the SCN9A gene is the cause of PEM in this case. Combination therapy of aspirin, rizatriptan benzoate, mexiletine hydrochloride, carbamazepine and local treatment can effectively control the symptoms of PEM, reduce the frequency of acute attacks and improve the prognosis.